2010
DOI: 10.1002/ajmg.a.33222
|View full text |Cite
|
Sign up to set email alerts
|

Identification of susceptibility loci for scoliosis in FIS families with triple curves

Abstract: The triple curve pattern (three lateral curvatures of equal severity) has been recognized as a distinct and unique clinical subtype of scoliosis. As part of a large study of familial idiopathic scoliosis (FIS), a subset of five families with a triple curve pattern (at least one member of each family having a triple curve) was evaluated to determine if this curve pattern was linked to any of the markers previously genotyped as part of the STRP-based previous linkage screen. Model independent linkage analysis (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…The current literature includes multiple studies that have used linkage and association analyses. Genome-wide linkage analyses have effectively localized candidate regions; however, progress has been burdened by heterogeneity both within and between study populations and by insufficient statistical power ( Wise et al 2000 ; Chan et al 2002 ; Salehi et al 2002 ; Justice et al 2003 ; Miller et al 2005 , 2006 ; Alden et al 2006 ; Ocaka et al 2008 ; Gurnett et al 2009 ; Raggio et al 2009 ; Clough et al 2010 ; Marosy et al 2010 ; Edery et al 2011 ). Association studies, including genome-wide association studies (GWAS), have implicated select genes, including CHD7 , LBX1 , and GPR126 ( Gao et al 2007 ; Sharma et al 2011 ; Takahashi et al 2011 ; Kou et al 2013 ).…”
mentioning
confidence: 99%
“…The current literature includes multiple studies that have used linkage and association analyses. Genome-wide linkage analyses have effectively localized candidate regions; however, progress has been burdened by heterogeneity both within and between study populations and by insufficient statistical power ( Wise et al 2000 ; Chan et al 2002 ; Salehi et al 2002 ; Justice et al 2003 ; Miller et al 2005 , 2006 ; Alden et al 2006 ; Ocaka et al 2008 ; Gurnett et al 2009 ; Raggio et al 2009 ; Clough et al 2010 ; Marosy et al 2010 ; Edery et al 2011 ). Association studies, including genome-wide association studies (GWAS), have implicated select genes, including CHD7 , LBX1 , and GPR126 ( Gao et al 2007 ; Sharma et al 2011 ; Takahashi et al 2011 ; Kou et al 2013 ).…”
mentioning
confidence: 99%
“…Recently, a genome-wide association study was performed in a Japanese population and three SNPs (single nucleotide polymorphisms), near LBX1 on 10q24.31, were associated with adolescent idiopathic scoliosis [Takahashi et al, 2011;Gao et al, 2013]. Indeed, LBX1 has been identified as a candidate gene for familial idiopathic scoliosis [Marosy et al, 2010]. Here, we describe the first case of the isolated microduplication of this gene.…”
Section: Introductionmentioning
confidence: 80%
“…Variable penetrance, underlying parental mosaicism, or the function of regulatory genes could explain the heterogeneity of these genetic alterations. Although LBX1 has been related to idiopathic scoliosis [Marosy et al, 2010;Takahashi et al, 2011;Gao et al, 2013], there are no cases with SHFM3 with described scoliosis, vertebrae malformations, or myopathy. Furthermore, 15% of SHFM3 patients have intellectual disability, usually severe [Elliott and Evans, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an association between a polymorphism of the FBN1 gene and AIS was not found [179]. Twenty-one candidate genes on chromosomes 6 and 10 were found in families with triple IS spine deformities [180]. Salehi et al [181] reported on the link between familial IS and 17p11 (D17S947-D17S798) gene polymorphism.…”
Section: Genetic Factors Study Of Ais In Twins Demonstratedmentioning
confidence: 99%